RISK MITIGATION FOR THE ADDITION OF PUBLIC ELECTRIC VEHICLE CHARGING STATIONS (SPKLU) AT PLN UP3 BOGOR - Warhamni Samahdina; Nazaruddin; Mailita Tryana Sembiring (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Petroleum as a result of current energy production, sooner or later petroleum will run out. For that, besides saving the use of energy from non-renewable natural resources, we must also look for alternative sources of new energy to meet energy needs that cannot be stopped anymore. Renewable electrical energy is energy that has a sustainable process such as solar power, wind power, water currents, geothermal energy, and biomass power. And currently the need for renewable electrical energy is important amidst the issue of global warming.